Why Do People Who Belong to the Same Clan Engage in the Same Entrepreneurial Activities?—A Case Study on the Influence of Clan Networks on the Content of Farmers’ Entrepreneurship - Jiang, Xiaoli; Ma, Xiao; Li, Zenian; Guo, Yongjin; Xu, Anxin; Su, Xiaofeng (Frontiers in Psychology, 2022)
Farmers’ entrepreneurship is a powerful breakthrough for solving the problems associated with “agriculture, rural areas and farmers.” Although studies have commonly used the same entrepreneurial activities to analyze farmers’ entrepreneurship, its deep economic roots have rarely been investigated. Investigating the internal development mechanism within the same industry is helpful for understanding farmers’ entrepreneurship motivation and decision making and is an important point at which to implement regional research and enrich the overall research on farmers’ entrepreneurship in the Chinese context. Based on a single-case study in Q Village, Fujian Province, this work identifies the key role played by relational contracts in entrepreneurship groups: reducing transaction costs, promoting investment in asset specificity, and improving contract flexibility. Moreover, this approach is conducive for different action groups in terms of stimulating entrepreneurial motivation in the initial entrepreneurship period and improving entrepreneurship learning ability in the long term. Primary Action Group transforms exploratory intuitive learning into exploratory compilation learning, and Secondary Action Group triggers the learning effect and makes a proprietary investment by utilizing intuitive formulaic learning and compiled formulaic learning, thus reducing unforeseen, contracting and verification costs. During the pattern maturity period, Primary Action Group rationally integrates the supply chain and forms a stable entrepreneurial paradigm, while Secondary Action Group does so to maintain prior information reserves and lower information search, supervised execution, and bargaining decision costs. The value cocreation ability of the same type of commercial modularity is formed, and the whole process of farmers’ entrepreneurship is completed. Our results have important implications for policymakers in China and other countries with clans.